A política curricular para o ensino de geografia no estado de Mato Grosso (2015 – 2018) - Cunha, Eduardo de Lima (2019)
This research focuses on the curriculum policy reconfiguration for elementary school, especially for the discipline of Geography, in the public school system of Mato Grosso, Pedro Taques’s government (2015-2018). It is being developed in the Postgraduate Program in Education (PPGEdu), in the Research Line Public Educational Policies and Pedagogical Practices and brings the following question: what senses of education and curriculum teaching are homogenized in the policy produced by Taques’s government for Geography in elementary school in Mato Grosso? In general, the research aims to analyze the curriculum, education and teaching senses hegemonized in the curriculum policy for Geography in the elementary school in Mato Grosso, from 2015 to 2018, once its organization by learning objectives was proposed as a measure for improving the education quality in the state. The research specific objectives are: 1. to characterize main aspects of the curriculum policy of Mato Grosso; 2. discuss and problematize the senses that embody the curriculum policy for Geography teaching. The research theoretical-methodological approach is based on the Policy Cycle of Stephen Ball, Richard Bowe and Annie Gold, which shows some decentralization of the powers that shape public policies. The questions related to the curriculum are punctuated from the poststructural studies of Alice Casimiro Lopes and Elizabeth Macedo, who understand curriculum as a practice of signification. The analysis of Mato Grosso's curriculum policy presents traces of an educational trend based on the teaching of contents, configured from learning objectives that constitute as determining elements of a results policy. In this sense, the research empirical is composed of curriculum documents such as: Pedagogical Orientation of 2016, for being a transitional milestone in the state educational policies; the Learning Objectives Assessment Launch Manual for Human Training Cycle Elementary School - Urban Schools; the Curriculum Matrix of Learning Objectives for the Urban Elementary Schools / 2017 and 2018. The theoretical perspectives that substantiate Geography teaching also interest this research. Without dissociating them from curriculum theorizing, I intend, in this production, to analyze the teaching trends of the school subject, based on the concepts of this science and similarly seek for the school subject's history connection with the different perspectives of curriculum theorizing.